Maturing Human CD127+ CCR7+ PDL1+ Dendritic Cells Express AIRE in the Absence of Tissue Restricted Antigens - Fergusson, Joannah R.; Morgan, Michael D.; Bruchard, Melanie; Huitema, Leonie; Heesters, Balthasar A.; van Unen, Vincent; van Hamburg, Jan Piet; van der Wel, Nicole N.; Picavet, Daisy; Koning, Frits; Tas, Sander W.; Anderson, Mark S.; et al. (Frontiers in Immunology, 2019)
Expression of the Autoimmune regulator (AIRE) outside of the thymus has long been suggested in both humans and mice, but the cellular source in humans has remained undefined. Here we identify AIRE expression in human tonsils and extensively analysed these “extra-thymic AIRE expressing cells” (eTACs) using combinations of flow cytometry, CyTOF and single cell RNA-sequencing. We identified AIRE+ cells as dendritic cells (DCs) with a mature and migratory phenotype including high levels of antigen presenting molecules and costimulatory molecules, and specific expression of CD127, CCR7 and PDL1. These cells also possessed the ability to stimulate and re-stimulate T cells and displayed reduced responses to toll-like receptor (TLR) agonists compared to conventional DCs. While expression of AIRE was enriched within CCR7+CD127+ DCs, single-cell RNA sequencing revealed expression of AIRE to be transient, rather than stable, and associated with the differentiation to a mature phenotype. The role of AIRE in central tolerance induction within the thymus is well established, however our study shows that AIRE expression within the periphery is not associated with an enriched expression of tissue-restricted antigens (TRAs). This unexpected finding, suggestive of wider functions of AIRE, may provide an explanation for the non-autoimmune symptoms of APECED patients who lack functional AIRE.